Moving Microbiome Science from the Bench to the Bedside: a Physician-Scientist Perspective - Neeraj K. Surana (American Society for Microbiology, 2019)
ABSTRACT The recognition over the past decade that nearly all diseases are associated with changes in the microbiome has raised hope that microbiome-based therapeutics may cure many human ailments. Billions of dollars are being poured into microbiome-oriented biotech companies, and the coming years will undoubtedly witness the approval of the first generation of these products. However, significant hurdles remain in expanding the pipeline and advancing these first-generation therapies. In this perspective, I will discuss the challenges related to identifying causal microbes, determining their mechanism of action, and characterizing the specific bacterial molecules required for disease protection. We are approaching these issues through a combination of clinical sampling, animal models, classic microbiology methodologies, and systems-based approaches. The field of microbiome research is on the cusp of being able to identify clinically actionable host-microbe relationships; increasing attention on identifying causal microbes and their bioactive factors will usher in the next generation of microbiome-based therapies.